Current practice of intracranial pressure monitoring in children with severe traumatic brain injury—a nationwide prospective surveillance study in Germany - Brensing, Pia; Greve, Sandra; Hojeij, Rayan; Dammann, Philipp; Felderhoff-Müser, Ursula; Dohna-Schwake, Christian; Bruns, Nora (Frontiers in Pediatrics, 2024)
Background: For management of severe traumatic brain injuries (sTBI) in children, the overall level of evidence to guide diagnostic and therapeutic procedures is low. Since 2016, international guidelines have subsequently suggested invasive intracranial pressure (ICP) monitoring in patients with initial Glasgow Coma Scale (GCS) ≤8. In Germany, ICP monitoring was an individual case decision from 2011 until the 2022 update of the German pediatric TBI guideline. The aim of this study was to evaluate current clinical practice of invasive ICP monitoring in Germany in children <10 years with respect to guideline recommendations.Methods: Anonymized clinical data on sTBI cases <10 years of age were collected in a nationwide prospective surveillance study via the German Pediatric Surveillance Unit ESPED from July 2019 until June 2022. Inclusion criteria for the surveillance study were sTBI (initial GCS ≤8) or neurosurgery following TBI. For this analysis, only cases with GCS ≤8 were subject to the present analysis. Descriptive analyses were performed to assess the proportion of ICP monitored patients and describe the cohort.Results: Out of 217 reported cases, 102 cases met the inclusion criteria and thus qualified for ICP monitoring. Of these, 37 (36 %) received ICP monitoring. Monitored patients were older, had lower median GCS values at presentation (4 vs. 5), higher mortality (32 % vs. 22 %), and were more frequently diagnosed with cerebral edema (68 % vs. 37 %).In children <10 years with sTBI, the present clinical management regarding ICP monitoring deviates from the current German national and international guidelines. The reasons remain unclear, with the low level of evidence in the field of ICP monitoring and the recency of changes in guideline recommendations as potential contributors. Prospective interventional studies should elucidate the benefit of ICP monitoring and ICP directed therapies to provide evidence-based recommendations on ICP monitoring.